2010
DOI: 10.1111/j.1539-6924.2010.01425.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Expert Models in Human Reliability Analysis-A Dependence Assessment Method Based on Fuzzy Logic

Abstract: In human reliability analysis (HRA), dependence analysis refers to assessing the influence of the failure of the operators to perform one task on the failure probabilities of subsequent tasks. A commonly used approach is the technique for human error rate prediction (THERP). The assessment of the dependence level in THERP is a highly subjective judgment based on general rules for the influence of five main factors. A frequently used alternative method extends the THERP model with decision trees. Such trees sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…The idea behind the work in [28] and [29] is to build a computable model that represents the relationships among the relevant factors 5 (for the present application, relevant to the dependence between two events) and between these factors and the HEP. The potential benefits from the use of expert models in HRA (connected with possible increased transparency and repeatability of HRA analysis) have been discussed by the authors of the present paper in [27].…”
Section: Expert Systems For Human Error Dependence Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The idea behind the work in [28] and [29] is to build a computable model that represents the relationships among the relevant factors 5 (for the present application, relevant to the dependence between two events) and between these factors and the HEP. The potential benefits from the use of expert models in HRA (connected with possible increased transparency and repeatability of HRA analysis) have been discussed by the authors of the present paper in [27].…”
Section: Expert Systems For Human Error Dependence Assessmentmentioning
confidence: 99%
“…A discussion of the limitations of current approaches for human error dependence treatment is beyond the scope of the present paper (see [27] for more details). The idea behind the work in [28] and [29] is to build a computable model that represents the relationships among the relevant factors 5 (for the present application, relevant to the dependence between two events) and between these factors and the HEP.…”
Section: Expert Systems For Human Error Dependence Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Deacon et al (2013) implemented a combination of expert judgment techniques for evaluating the risk during the evacuation opreration. Further, Podofillini et al (2010) proposed a fuzzy expert system (FES) formalism for dependence assessment in HRA, which captures the rules used by experts to assess dependence levels and incorporates this knowledge into an algorithm and software tool. Zio et al (2009) suggested HRA framework, which is based on a fuzzy expert system in which a set of transparent fuzzy logic rules is used to represent the relationship between the input factors and the conditional human error probability.…”
Section: Introductionmentioning
confidence: 99%